Basic sources of electric and magnetic fields newly examined. - Scott Bennett, W. (IEEE Antennas & propagation magazine.)
The current element and the physical origins of its electric and magnetic fields are simply explained. In the course of the discussion, Coulomb's law and the Biot-Savart law are extended to include the time-varying point sources that make up a current element.